DEVELOPMENT OF THE AXIOSPHERE OF THE FUTURE TEACHER IN THE DIALOGUE SPACE OF MODERN EDUCATION - N. A. Astashova; S. K. Bondyreva; A. P. Smantser (Russian State Vocational Pedagogical University, 2018)
Introduction. The vector of development of the education system, the choice of its contents, quality and results of training, style and spirit of the relationship of its participants, degree of their informative activity, intellectual and cultural growth are firstly caused by valuable attitudes of participants of the educational process. A teacher is a bearer of values. One of the main functions of the teacher is the education of the younger generation, the introduction of the person to moral ethics and universal values. In this regard, training of future teachers has to include the purposeful formation of the system of the internal, emotionally experienced values which will help them to cope with the complex of socio-cultural problems in the future professional activity.The aim of the paper is to present the research findings on the conceptual model of the dialogue space of education as the basis for the development of the future teacher axiosphere which corresponds to current ideological, social, economic, technological and other progressive civilization trends.Methodology and research methods. In the course of the research, fundamental ideas of the following scientific approaches were applied: humanistic approach - free and creative development of an individual; dialogical approach - pluralism of opinions and a variety of positions of subjects of education; axiological approach - attitude of the individual to the world around him/her, to other people and to himself / herself; activity approach - specific activity of the individual, aimed at appropriation of social experience by the person, change of the surrounding world and selfhood. To design and organize the model of the dialogue space, the methods of analysis, synthesis and generalization of the theory and practice were used.Results and scientific novelty. The authors presented the strategic guidelines of the interactive environment education: the development of social cooperation, using the pedagogical peaceful potential, the development of interpersonal and intergroup relations, organizing children spiritual and moral education as a national priority. The teacher value system was revealed empirically and described. It was found out that a modern teacher should responsibly perform the professional duties of a mentor, tutor and facilitator of the educational process. The authors clarified the concept of "axiological sphere" of the teacher. The teacher axiological sphere is considered as a complex of personal, professional-pedagogical and socio-cultural values. These values have separable functions. Firstly, they determine the content and nature of the educational activity. Secondly, they regulate the interaction of the participants of the educational activity. Thirdly, they stimulate personal self-expression of the members of that activity. Fourthly, they directly influence the efficiency and effectiveness of education.The conceptual model of dialogue space of education as a formation zone for the teacher's axiosphere was designed on the basis of the theoretic-methodological, philosophical, psychological and pedagogical concepts of the leading scholars' writings. The resources of this space were identified; its structural components were presented and proved. The implementation of the components mentioned above can create a special context for the humanitarian training of a future teacher; will give an opportunity of interactive development of students' common cultural, communicative and special competencies; will increase students' motivation to pedagogical activity, the search of new ideas for training, innovations and professional self-education. The authors demonstrated the value orientations typology and tactics of their acquisition by students at the dialogue level.Practical significance. The presented materials can be used in practice of the higher pedagogical education to improve the quality of graduates' training through enrichment of their personality axiological sphere. The model for the formation of the future teachers' value system in dialogue educational space will allow providing conditions for individualization of routes of their training taking into account different approaches to the organization of activity of education participants and features of their self-development.